Empowering the young of Europe to meet labour market challenges : findings from study visits 2009/10 - (:unkn) unknown (Publications Office of the European Union, 2011)
"This publication presents findings from 53 study visits during 2009/10 focused on preparing and supporting youth integration into the labour market and reducing unemployment among young people. This is one of European priorities supported by the Youth on the move initiative which focuses on policies and practices to support flexible learning modes and pathways for young people, easing their transition from education and training to the labour market and developing their entrepreneurial skills and competences. Group reports prepared by participants during the study visits were the main information source, from which 35 successful initiatives were selected." (Hrsg., BIBB-Doku)
Keywords: I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.2.3.2 Anforderungen & Bedarfe; I 2.2 Europa; EU-Programm; Bildungspersonal; Best practice; Berufseinmündung; Zweite Schwelle; Unternehmerische Qualifikation; Europa